Application of the magnetoresistive sensor for displacement measurement - Soh, Kim Fai. (2009)
An experimental rig was designed and successfully built to perform static and dynamic calibrations of the Philips magnetoresistive sensor. Characteristic of the sensor was also evaluated. A larger linear range can be achieved by having the sensor's transverse magnetic field pointing towards the stainless steel target. The measuring system behaves linearly with the variation of air gap from 0 to 0.46mm. The sensitivity of the measurement system is about 3 milivolts per micron of air gap variation. In terms of dynamic response, the magnetoresistive sensor performs as well as the commercially available Bently Nevada 5mm eddy curent displacement probe.